Faktor penentu kesuksesan bisnis digital startup - Latif, Vinka Tania; Widoatmodjo, Sawidji (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The increasing importance of startup ventures in the global economy not only indicates the strengthening of the business environment but has also paved the way for the expansion of the digital industry and opened a new window of opportunity for digital businesses. The development of startups in Indonesia is quite rapid, but the increasing development of the number of startups is also proportional to the number of failures that befall startups. So, the purpose of this study is to find the determinants that affect the success of digital startups. To be able to obtain the research objectives, the researcher conducted a literature analysis to find out the variables of the determinants of digital startup business success. Researchers analyzed the data obtained using the AHP analysis method. AHP analysis is useful for obtaining determining factors, so from 45 respondents, the research results show that entrepreneur competence is the most important determining factor. Keadaan peningkatan pentingnya startup ventura dalam ekonomi global tidak hanya menunjukkan penguatan lingkungan bisnis tetapi juga telah membuka jalan bagi perluasan industri digital dan membuka jendela peluang baru untuk bisnis digital. Melihat perkembangan startup di Indonesia memang cukup pesat, namun meningkatnya perkembangan jumlah startup tersebut juga sebanding dengan angka kegagalan yang menimpa startup. Sehingga tujuan dari penelitian ini adalah menemukan faktor penentu yang memengaruhi kesuksesan digital startup. Untuk dapat memperoleh tujuan penelitian, maka peneliti melakukan analisis literatur untuk mengetahui variabel dari faktor penentu kesuksesan bisnis digital startup. Peneliti melakukan analisis data yang diperoleh dengan menggunakan metode analisis AHP. Analisis AHP berguna untuk mendapatkan faktor penentu, maka dari 45 responden didapatkan hasil penelitian yaitu kompetensi pengusaha merupakan faktor penentu yang paling penting.